2008
DOI: 10.2215/cjn.02470607
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcome of Patients with Systemic Amyloidosis Undergoing Dialysis

Abstract: Conclusions: Survival of patients with amyloidosis undergoing dialysis, especially AL type, is probably better than previously reported. However, mortality is higher in AL than AA type, especially in the setting of cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…Survival of patients with ALA was comparable with data from the Australia and New Zealand Dialysis and Transplant Registry, comprising 490 patients with ALA or amyloid A (AA) amyloidosis on chronic dialysis (16), and a smaller French cohort of patients with ALA (17). Survival was better (39 months) in a British cohort of 221 patients with ALA (10) but worse (11 months) in an Italian cohort of 59 patients (18).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Survival of patients with ALA was comparable with data from the Australia and New Zealand Dialysis and Transplant Registry, comprising 490 patients with ALA or amyloid A (AA) amyloidosis on chronic dialysis (16), and a smaller French cohort of patients with ALA (17). Survival was better (39 months) in a British cohort of 221 patients with ALA (10) but worse (11 months) in an Italian cohort of 59 patients (18).…”
Section: Discussionmentioning
confidence: 53%
“…Frailty has already been described as an independent risk factor of mortality in chronic dialysis (22,23), and CHF is a major prognostic factor in patients with ALA (17). The surprising association of high BP at the initiation of dialysis with a reduced risk of death has been reported before in dialysis (24) and could be of particular relevance in patients with ALA, where low BP can be caused by CHF or dysautonomia.…”
Section: Discussionmentioning
confidence: 81%
“…Esteve et al found that survival time in AL patients was shorter than in those with secondary amyloidosis (AA): 58% and 19% at 12 and 24 month vs 55% and 44%, respectively [3]. Bollée et al also observed that median survival in AL dialyzed patients was only 26 months [9]. A long-term survival of patients with primary amyloidosis was described by Kyle et al, who observed 10 years or more survival in 4.7% of 810 patients with AL [10].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observation in the current case: the female lost the possibility to be treated by PD because of peritonitis. Esteve et al found that mean the survival time of 12 and 24 months after the start of dialysis was 30% and 5%, respectively [9]. Gude et al have also described a case of short-time PD treatment in primary amyloidosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Time from diagnosis to dialysis is shorter for AL than for AA amyloidosis. Mean time to dialysis in AL amyloidosis was 15 months, mean survival on dialysis was 24 months; mortality is signifi cantly higher in patients with AL than with AA amyloidosis [30]. Hemodialysis in AL amyloidosis is complicated by a strong tendency towards intradialytic hypotension due to cardiac involvement, continuous ambulatory peritoneal dialysis by peritonitis [31].…”
Section: Renal Replacement Therapy In Amyloidosismentioning
confidence: 99%